2017
DOI: 10.1073/pnas.1708427114
|View full text |Cite
|
Sign up to set email alerts
|

Histone phosphorylation by TRPM6’s cleaved kinase attenuates adjacent arginine methylation to regulate gene expression

Abstract: TRPM6 and TRPM7 are members of the melastatin-related transient receptor potential (TRPM) subfamily of ion channels. Deletion of either gene in mice is embryonically lethal. TRPM6/7 are the only known examples of single polypeptides containing both an ion channel pore and a serine/threonine kinase (chanzyme). Here we show that the C-terminal kinase domain of TRPM6 is cleaved from the channel domain in a cell type-specific fashion and is active. Cleavage requires that the channel conductance is functional. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…In addition to its role in regulating tissue growth, the pathway was implicated in the control of other biological processes, such as cell-fate determination, mitosis, and pluripotency [67]. The TRPM6 gene was enriched in the mineral absorption pathway; TRPM6 is a member of the melastatin-related transient receptor potential (TRPM) subfamily of ion channels, and it is a polypeptide containing both an ion channel pore and a serine/threonine kinase [68]. Studies in mice showed these channels to have a role in whole-body magnesium homeostasis, as well as additional critical functions during early embryogenesis [69].…”
Section: Gene Ontology and Metabolic Pathwaysmentioning
confidence: 99%
“…In addition to its role in regulating tissue growth, the pathway was implicated in the control of other biological processes, such as cell-fate determination, mitosis, and pluripotency [67]. The TRPM6 gene was enriched in the mineral absorption pathway; TRPM6 is a member of the melastatin-related transient receptor potential (TRPM) subfamily of ion channels, and it is a polypeptide containing both an ion channel pore and a serine/threonine kinase [68]. Studies in mice showed these channels to have a role in whole-body magnesium homeostasis, as well as additional critical functions during early embryogenesis [69].…”
Section: Gene Ontology and Metabolic Pathwaysmentioning
confidence: 99%
“…It has been demonstrated that inactivation of TRP genes by aberrant methylation (hyper-and hypo-methylation) of GC-rich DNA regions, CpG islands, is suggested to be involved in tumor development and progression. In this regard, hydrogen peroxide has been found to induce demethylation of the TRPM2 promoter region and increase the expression of TRPM2 in melanocytes [113]; the TRPM6 and TRPM7 ion channels have been found to bind to the chromatin-remodeling complexes, induce histone phosphorylation, and decrease arginine methylation, resulting in changes in the transcription of hundreds of genes [114,115]; transactivation of TRPA1 promoter by Notch1 receptor intracellular domain, which promotes TRPA1 expression in erytroleukemic cells, suppresses erythroid differentiation [116]. Moreover, regarding cancer chemoresistance, miR-320a is a mediator of the chemoresistance of BC cells by targeting TRPC5 and NFATc3 and the expression of miR320a is regulated by methylation of its promoter and the transcription factor, v-ets erythroblastosis virus E26 oncogene homolog 1 [117].…”
Section: Discussionmentioning
confidence: 99%
“…Protein arginine methylation is a post-translational modification (PTM) that regulates the cell cycle 1 , metabolism 2,3 , signal transduction [4][5][6] , and transcriptional control [7][8][9][10][11] . Arginine methylation is catalyzed by protein arginine methyltransferases (PRMTs) and occurs in three forms, monomethylarginine (MMA), asymmetric dimethylarginine (ADMA), and symmetric dimethylarginine (SDMA).…”
Section: Introductionmentioning
confidence: 99%